Local MicroRNA Modulation Using a Novel Anti-miR-21–Eluting Stent Effectively Prevents Experimental In-Stent Restenosis. Issue 9 (September 2015) - Wang, Dong; Deuse, Tobias; Stubbendorff, Mandy; Chernogubova, Ekaterina; Erben, Reinhold G.; Eken, Suzanne M.; Jin, Hong; Li, Yuhuang; Busch, Albert; Heeger, Christian-H.; Behnisch, Boris; Reichenspurner, Hermann; et al.
Abstract : Objective—: Despite advances in stent technology for vascular interventions, in-stent restenosis (ISR) because of myointimal hyperplasia remains a major complication. Approach and Results—: We investigated the regulatory role of microRNAs in myointimal hyperplasia/ISR, using a humanized animal model in which balloon-injured human internal mammary arteries with or without stenting were transplanted into Rowett nude rats, followed by microRNA profiling. miR-21 was the only significantly upregulated candidate. In addition, miR-21 expression was increased in human tissue samples from patients with ISR compared with coronary artery disease specimen. We systemically repressed miR-21 via intravenous fluorescein-tagged-locked nucleic acid-anti-miR-21 (anti-21) in our humanized myointimal hyperplasia model. As expected, suppression of vascular miR-21 correlated dose dependently with reduced luminal obliteration. Furthermore, anti-21 did not impede reendothelialization. However, systemic anti-miR-21 had substantial off-target effects, lowering miR-21 expression in liver, heart, lung, and kidney with concomitant increase in serum creatinine levels. We therefore assessed the feasibility of local miR-21 suppression using anti-21–coated stents. Compared with bare-metal stents, anti-21–coated stents effectively reduced ISR, whereas no significant off-target effects could be observed. Conclusion—: This study demonstrates the efficacy of an anti-miR–coated stent for the reduction of ISR. Abstract : Supplemental Digital Content is available in the text.